2019
DOI: 10.1021/jacs.9b00688
|View full text |Cite
|
Sign up to set email alerts
|

Automated Stoichiometry Analysis of Single-Molecule Fluorescence Imaging Traces via Deep Learning

Abstract: The stoichiometry of protein complexes is precisely regulated in cells and is fundamental to protein function. Singe-molecule fluorescence imaging based photobleaching event counting is a new approach for protein stoichiometry determination under physiological conditions. Due to the interference of the high noise level and photoblinking events, accurately extracting real bleaching steps from single-molecule fluorescence traces is still a challenging task. Here, we develop a novel method of using convolutional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
90
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(91 citation statements)
references
References 52 publications
(90 reference statements)
1
90
0
Order By: Relevance
“…It simultaneously displays highly sensitive FL lifetime response, strong absorption in the visible region, and high photostability, which will open up new possibilities in long-time and super-resolution microscopy observation for mapping local environments and/ or molecular communications. [17,18] Since synthetic approaches to water-soluble perylene dyes have been already established, [15] the flapping peryleneimides also have a potential for biological applications as sensitive fluorescent probes in a low-viscosity region. [26]…”
Section: Angewandte Chemiementioning
confidence: 99%
“…It simultaneously displays highly sensitive FL lifetime response, strong absorption in the visible region, and high photostability, which will open up new possibilities in long-time and super-resolution microscopy observation for mapping local environments and/ or molecular communications. [17,18] Since synthetic approaches to water-soluble perylene dyes have been already established, [15] the flapping peryleneimides also have a potential for biological applications as sensitive fluorescent probes in a low-viscosity region. [26]…”
Section: Angewandte Chemiementioning
confidence: 99%
“…We believe that the developed method of testing algorithms with semi-synthetic data will be highly useful, not only for benchmarking other PBSA algorithms, but also to generate training data for machine learning based approaches. 20 Using ATTO 647N-labelled structures with a known stoichiometry in vitro, we showed that quickPBSA yields highly accurate (<10% deviation across all samples) estimates of All data was background corrected by subtracting a constant offset from acquired image series to account for excitation light bleedthrough and sample autofluorescence. Offsets were manually determined for each sample and were well reproducible within one condition, but varied between conditions.…”
Section: Resultsmentioning
confidence: 95%
“…Recently molecular counting via photobleaching has attracted renewed attention due to the development of novel analysis modalities based on Bayesian statistics 18,19 and machine learning. 20 But these novel methods are demanding in terms of data quality, which in turn leads to new requirements regarding fluorophore properties. In the trade-off between signal-tonoise ratio (SNR) of the individual bleaching steps and the rate at which photobleaching occurs, bright and stable fluorophores are advantageous.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Ty pically,t he input sensors have attracted considerable interest as processing units to detect and integrate multiple environmental signals. [3] Multiple-input logic operations are necessary for cells to ensure the accuracy of initiating ad esired response.F or example,t he beta cells regulate the secretion of insulin in response to different stimuli, such as glucose,g lucagon and hormones,a nd thereby maintain glucose homeostasis. [4] Thus,t here is al ong-standing interest in reprogramming cells to sense multiple-inputs and initiate specific cellular signal transduction as am imic of natural complex information processing.…”
Section: Living Cells Continuously Sense Various Extracellular Signalsmentioning
confidence: 99%